Dynamics of place, boundary and object encoding in rat anterior claustrum - Jankowski, Maciej M.; O’Mara, Shane M. (Frontiers in Behavioral Neuroscience, 2015)
Discrete populations of brain cells signal differing types of spatial information. These “spatial cells” are largely confined to a closely-connected network of sites. We describe here, for the first time, cells in the anterior claustrum of the freely-moving rat encoding place, boundary and object information. This novel claustral spatial signal potentially directly modulates a wide variety of anterior cortical regions. We hypothesize that one of the functions of the claustrum is to provide information about body position, boundaries and landmark information, enabling dynamic control of behavior.